(untitled) (Journal of Tourism and Himalayan Adventures, 2019)
In this study, the impact of business model innovation on the sustainability of tourism activities is discussed in detail. The methodology of the paper is literature review based on previous investigation in the domain of business model innovation and the critical evaluation of the findings. The manuscript starts with brief information regarding to previous findings in the existing literature, then the relationship between business model innovation and sustainability of tourism activities is investigated with a specific focus on rapidly changing dynamics of world and therefore the transformative aspects of business strategies are the main objective of the study. Next, the manuscript suggests a model where the effect of business model innovation is modeled in a mathematical form, pertaining to several variables including technological development, total revenues, and the degree of environmental degradation. Finally, the manuscript concludes that the innovation-based nature of tourism sector requires firms to constantly innovate their business models so that they can arrange themselves according to necessities of rapidly changing business environment, in order to preserve their competitiveness and maintain their business activities to keep making profits.